Lesotho : An Assessment of the Investment Climate - World Bank (Washington, DC, 2012)
The objective of the Lesotho Investment Climate Assessment (ICA) is to evaluate the investment climate in Lesotho in all its operational dimensions and promote policies to strengthen the private sector. By comparing the investment climate in Lesotho to investment climates in other countries, it is possible to observe areas were Lesotho performs relatively well and others were improvements is necessary if Lesotho is to continue to grow. The primary source for the assessment is a firm level survey (investment climate survey or ICS) which was completed towards the end of 2004. About 110 firms in three sectors of the economy (manufacturing, construction and tourism) were interviewed. The information collected during the survey is supplemented with results from other studies conducted by the Bank and other donor agencies and the Government of Lesotho. In this study, the investment climate in Lesotho is compared other countries, particularly attention is given to China and India because they are important competitors in Lesotho's main export market, the garment sector. Chapter 5, attempts to provide key recommendations to assist the Government in addressing current weakness and improving environment for a faster and more diversified economic growth.